An education intervention in a professional female basketball team and coaching staff improves sleep and alertness - Dunican, I. C.; Caldwell, J. A.; Morgan, D.; Stewart, A.; Eastwood, P. R. (Translational Sports Medicine, 2021)
The objectives of this study were to quantify the sleep behaviours and alertness of female basketball players and coaches and deploy a sleep education program. Twelve female players and three male coaches wore actigraphy devices for 60 nights during the Women`s National Basketball League, Australia to assess sleep and alertness and completed questionnaires assessing daytime sleepiness, insomnia, and sleep apnoea. Players and coaches participated in a sleep education program consisting of a 2-hour sleep education session and a 20-min individual consultation to identify improvements to sleep behaviours. There were no statistical changes when comparing post to pre-intervention data for players after the sleep education program. Whereas statistical significance was observed in the coaches with an earlier time of sleep onset (p=0.04), increase in sleep duration (p<0.05) increase in time in bed (p<0.05). The wake-up time each morning was later by 31 mins (p<0.05). No player or coach was at risk for sleep apnea or daytime sleepiness. Three athletes identified with having insomnia symptoms. This study provides evidence that an intervention comprised of a group education session and individual consultations are relevant for the maintenance or improvement of sleep habits and behaviours in a team-sport context.